2017
DOI: 10.1002/brb3.756
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the effects of probiotic supplementation on neuropsychological performance and microRNA‐29a‐c levels in antiretroviral‐treated HIV‐1‐infected patients

Abstract: Introduction: The gut microbiota is involved in the regulation of cognition, mood, anxi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Experimental evidence has shown that lipopolysaccharides can alter the blood-brain barrier permeability [ 16 ], possibly leading to leakage of the serum pro-inflammatory milieu into the CSF, precipitating local inflammation. In this sense, several studies have shown that the gut microbiota and its products play central regulatory roles in this bidirectional relationship between the enteric and the central nervous system and on gut-brain axis [ 17 , 18 , 19 , 20 , 21 , 22 ]. The administration of probiotics to correct dysbiosis reduces microbial translocation, systemic inflammation and, possibly, the subsequent blood-brain barrier permeability, thus exerting an ameliorative effect on intrathecal immune activation and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has shown that lipopolysaccharides can alter the blood-brain barrier permeability [ 16 ], possibly leading to leakage of the serum pro-inflammatory milieu into the CSF, precipitating local inflammation. In this sense, several studies have shown that the gut microbiota and its products play central regulatory roles in this bidirectional relationship between the enteric and the central nervous system and on gut-brain axis [ 17 , 18 , 19 , 20 , 21 , 22 ]. The administration of probiotics to correct dysbiosis reduces microbial translocation, systemic inflammation and, possibly, the subsequent blood-brain barrier permeability, thus exerting an ameliorative effect on intrathecal immune activation and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a relatively new field of research is the investigation of the role of endocrinological and nutritional factors in episodic memory impairment in HIV infection. For instance, it has been shown that, in patients with HIV infection, both verbal and visual episodic memory performance, tested with RAVLT and the Rey‐Osterrieth Complex Figure Test (ROCFT), respectively, can be modulated by regulation of the gut microbiota through nutritional supplementation .…”
Section: Resultsmentioning
confidence: 99%
“… reported an association of memory performance, but not of psychomotor speed, with the presence of detectable HIV RNA in plasma. Interestingly, in patients with long‐term virological suppression (< 50 copies/mL) and CD4 counts > 400 cells/μL, a regulatory effect of the gut microbiota (modulated with nutritional supplementation) was found on both verbal and visual episodic memory performance .…”
Section: Resultsmentioning
confidence: 99%
“…About 20 mL of whole blood was collected by venipuncture in Vacutainer tubes containing EDTA (BD Biosciences, San Jose, CA, USA) at each study visit. Peripheral blood mononuclear cells were separated by Ficoll gradient centrifugation (Lympholyte; Cedarlane Labs, Hornby, ON, Canada) and washed twice in phosphate-buffered saline solution (Ceccarelli et al 2017b). Freshly isolated PBMCs were used immediately for immune phenotyping and activation staining.…”
Section: Specimen Processingmentioning
confidence: 99%